Comparison of the cardio-respiratory effects of methadone and morphine in conscious dogs - Maiante, A. A. [UNESP]; Teixeira Neto, Francisco José [UNESP]; Beier, S. L.; Corrente, J. E. [UNESP]; Pedroso, C. E. B. P. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The effects of methadone and morphine were compared in conscious dogs. Six animals received morphine sulfate (1 mg/kg) or methadone hydrochloride (0.5 mg/kg [MET0.5] or 1.0 mg/kg [MET1.0]) intravenously (i.v.) in a randomized complete block design. Cardiopulmonary variables were recorded before (baseline), and for 120 min after drug administration. One outlier was not included in the statistical analysis for hemodynamic data. Morphine decreased heart rate (HR) compared to baseline from 30 to 120 min (-15% to -26%), while cardiac index (CI) was reduced only at 120 min (-19%). Greater and more prolonged reductions in HR (-32% to -46%) and in CI (-24% to -52%) were observed after MET1.0, while intermediate reductions were recorded after MET0.5 (-19 to -28% for HR and -17% to -27% for CI). The systemic vascular resistance index (SVRI) was increased after methadone; MET1.0 produced higher SVRI values than MET0.5 (maximum increases: 57% and 165% for MET0.5 and MET1.0, respectively). Compared to morphine, oxygen partial pressure (PaO(2)) was lower (-12% to -13%) at 5 min of methadone (0.5 and 1.0 mg/kg), while carbon dioxide partial pressure (PaCO(2)) did not change significantly. It was concluded that methadone induces cardiovascular changes that are dose-related and is a more potent cardiovascular depressant agent than morphine in conscious dogs.